Investigation of genetic diversity in irradiated maize lines and its relation to hybrid performance - Bódi, Zoltán; Pepó, Pál; Zubor, Ákos; Tóth, Szilárd; Prokisch, József; Győri, Zoltán (Acta Agraria Debreceniensis, 2006)
Knowledge of genetic diversity among available parental lines is fundamental for successful hybrid maize breeding. The aims of this study were to estimate (1) genetic similarity (GS) and genetic distance (GD) (based on Jaccard index) in four maize inbreed lines; (2) to classify the lines according to their GD and GS; (3) to determine hybrid performance based on GD and heterosis for yield ability in 4x4 full diallel system. We used morphological description and AFLP (amplified fragment length polymorphisms) for estimation genetic polymorphism in four maize inbred lines. We estimated the applicability of genetic similarity in SC and reciproc hybrids for prediction of their performance.Three primer combinations were used to obtain AFLP markers, producing 207 bands, 70 of whit were polimorphic. The dendogram based on genetic similarities (GS) and genetic distance (GD) and morphological description separated four inbred lines into well-defined groups. Morphological description just with AFLP analysis showed reliable results. In view of genetic distance, the UDL 1 line and their linear and reciprocal crosses showed significant heterosis effect, which was confirmed by heterosis calculation based on grain yield.